Pengaruh Breast Care Dan Pumping Elektrik Terhadap Produksi Air Susu Ibu (ASI) Pada Pasien Post Sectio Caesarea Di RSIA Murni Teguh Rosiva Medan - Sari, Winda Permata; Simatupang, Lenny Lusia (Universitas Murni Teguh, 2025)
Sectio Caesarea can affect breast milk production after delivery. Breast care techniquesand electric pumping are thought to increase the production of post-sectio caesareanmothers. The objective of this study is to determine the effect of breast care and electricpumping on the production of breast milk in Post Sectio Caesarean patients. This study isa quasi-experimental study using a one group pretest and posttest design. The study wasconducted at the Murni Teguh Rosiva Mother and Child Hospital. The population was 33people and all of them were used as samples. Sampling by accidental sampling. Data wereanalyzed using the paired sample t-test. This study shows that breast milk production inpost-SC patients before being given breast care and electric pumping treatment (pretest)was entirely <100 ml/day (100.0%). After being given breast care and electric pumpingtreatment (posttest), it increased to 101-300 ml/day (69.7%). There is an effect of breastcare and electric pumping on breast milk production in post-SC mothers at RSIA MurniTeguh Rosiva, obtained p-value = 0.000 < 0.05 and t value = -14.527. It is concluded thatBreast care and electric pumping are effective for increasing breast milk production for post-sectio caesarean mothers. It is recommended further researchers are to conduct researchon increasing breast milk production with lactation massage, consumption of katuk leaves,and others.